Techno-Economic Analysis of Stand-Alone Hybrid Energy System for the Electrification of Iran Drilling Oil Rigs - Abdullah Asuhaimi Mohd Zin; Mehdi Moradi; Jalal Tavalaei; Amirreza Naderipour; Amir Hesam Khavari; Mohammad Moradi (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2017)
This paper explores the potential of use of stand-alone hybrid wind/solar energy system in electrification of calibrating equipment of drilling oil rig in Iran. To achieve this, different hybrid energy system configurations based on calibration equipment demand are proposed. This study puts emphasis on the energy production and cost of energy from both wind turbine and photovoltaic (PV) in the hybrid system. In addition, to make conditions more realistic, the real meteorological data is used for HOMER software to perform the technical and economic analysis of the hybrid system. Results indicate that the PV array shares more electricity production than the wind turbine generator if both wind turbine and PV array are utilized in the wind/solar hybrid system. Moreover, results show that the operational cost will be reduced by the suggested hybrid system.